Friday

August 1, 2014

August 1, 2014

Posted by **Serra** on Monday, August 20, 2007 at 9:16am.

-x2-5x-6

x=-3

x=-2

I got 0 for the first one and 0 for the second. Am I figuring them wrong? (and that is an x squared, not 2x)

-(-3)^2 -5(-3)-6

-(9)+15-6=0

Thanks!

you are right in both cases

-x^2-5x-6

=-(x^2+5x+6)

=-(x+2)(x+3)

notice if this had been an equation equal to zero,

x=-2 and x=-3 would have been solutions.

That is why both values gave you a zero answer.

**Related Questions**

ALGEBRA - Find all positive values for k for which each of the following can be ...

Algebra - Complete the table for each function. 1. f(x) = √x The x values ...

math - algebra - find the values of each of the following polynomials for the ...

Math - Q.1)If one zero of the polynomial 3x2-kx-2 is 2 find the other zero.allso...

domain - How do you find the domain of log(x^2-4)? and how about this one? e^(3x...

Maths - The question is "Show that z-2 is a factor of P(z)= z^3+mz^2+(3m-2)z-10m...

Pre-Algebra [repost ] - I need help on these three questions BEFORE 10:00 PM. ...

calc - one more question!! what values of c deos the polynomial f(x) = x^4 + cx^...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...